Breastfeeding Initiation Trends by WIC Participation and Race/Ethnicity Among Low-Income Women in 24 States, United States, 2009–2017. (14th June 2022) - Thoma, Marie; De Silva, Dane; Kim, Jinhee; Hodges, Leslie; Guthrie, Joanne
Abstract: Objectives: To describe long-term breastfeeding initiation trends by prenatal WIC participation and race/ethnicity among low-income women in the U.S. Methods: We used birth certificate data (2009–2017) for 24 states that adopted the 2003 birth certificate revision by 2009. The analytic sample included term births with hospital costs covered by Medicaid. Descriptive characteristics of WIC participants and WIC-eligible nonparticipants were assessed by year and race/ethnicity. Adjusted breastfeeding initiation prevalence was estimated using linear regression with county fixed effects, controlling for sociodemographic, obstetric, and health factors. Trends were compared by WIC status overall and within racial/ethnic groups. Results: Breastfeeding initiation increased for WIC participants and WIC-eligible nonparticipants (2009 to 2017). WIC participants had consistently lower breastfeeding initiation (2009: 68.6%; 2017: 78.0%) compared to nonparticipants (2009: 72.1%; 2017: 81.3%). The gap between WIC participants and nonparticipants narrowed more for Non-Hispanic Asian/Pacific Islander and non-Hispanic American Indian/Alaska Native women due to a larger increase among WIC participants (% Change: 32.4% and 12.9%, respectively) compared with nonparticipants (% Change: 11.4%, 6.4%). Conclusions: Breastfeeding statistics are often underrepresented among certain racial/ethnic groups, particularly for low-income populations. These findings can inform WIC and other maternal child health program efforts to improve breastfeeding initiation and reduce disparities. Funding Sources: This study was funded by cooperative agreement between the United States Department of Agriculture Economic Research Service and the University of Maryland, College Park. The findings and conclusions in this publication are those of the authors and should not be construed to represent any official USDA or US Government determination or policy.